Mesoscale structuring of gluten-free bread with starch. (April 2021) - Roman, Laura; Gomez, Manuel; Martinez, Mario M
Abstract : The gluten-free bread (GFB) market is steadily growing. Nonetheless, GFB-making still remains more of an art than a science. Although there are studies showing the effect of certain starchy materials on the final GFB quality, mechanistic understanding on the fundamental principles governing the mesoscale structural changes and interactions of starchy tissues during the different stages of processing is limited. This work highlights the importance of understanding GFB as a multistage, thermodynamically unstable system and the enormous potential of starchy ingredients to stabilize it (from batter to retail-packed long-self life GFB). This review will also expand on the structuring potential of starchy flour particles, starch granules and dispersed starch molecules to improve GFB quality in terms of loaf specific volume and crumb hardness, cohesiveness, elasticity and staling.